Relationship Between Lipoprotein (a) [Lp(a)] and Cognition in Different Ischemic Stroke Subtypes - Li, Jingjing; Li, Shiyu; Pan, Yuesong; Wang, Mengxing; Meng, Xia; Wang, Yilong; Zhao, Xingquan; Wang, Yongjun (Frontiers in Neurology, 2021)
Background and Purpose Although elevated serum Lipoprotein (a) [Lp(a)] is considered to be a risk factor of ischemic stroke, relationship between Lp(a) and cognitive impairment after stroke remains unclear. This study investigated the association of serum Lp(a) and cognitive function after acute ischemic stroke (AIS) or transient ischemic attack (TIA). Methods The study included 1017 patients diagnosed with AIS or TIA from cognition subgroup of the Third China National Stroke Registry (CNSR3). Montreal Cognitive Assessment (MoCA) at 2 weeks or discharge, 3 months and 1 year was evaluated. The primary outcome was cognitive impairment at 1 year, defined as MoCA≤22. The secondary outcome was cognition improvement at 1 year compared with 2 weeks. The association of Lp(a) levels and cognitive function was analyzed. Results Among 1017 patients included, 326 (32.1%) patients had cognitive impairment at 1 year. Patients with MoCA≤22 at 1 year were older, received less education, had higher baseline NIHSS, higher proportion of ischemic stroke history, large-artery atherosclerosis (LAA) subtype and multiple infarctions (P<0.05 for all). Patients of the highest Lp(a) quartile had slightly higher percentage of cognitive impairment at 1 year but without statistical difference. In subgroup analysis of LAA subtype, patients of the highest Lp(a) quartile had higher percentage of cognitive impairment at 1 year (adjusted OR:2.63; 95%CI:1.05-6.61, P<0.05). What’s more, patients of the highest Lp(a) quartile in LAA subtype had lower percentage of cognition improvement at 1 year. However, similar results were not found in small-artery occlusion (SAO) subtype. Conclusion Higher Lp(a) level might be associated with cognitive impairment and less cognition improvement at 1 year after AIS or TIA in patients of LAA subtype.